2018
DOI: 10.33314/jnhrc.v16i3.1177
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and practice of Computer Vision Syndrome among medical students and its impact on ocular morbidity

Abstract: Background: Computer vision syndrome is a common global problem among millions of computer users including medical students. Medical students are preferring soft copies rather than textbooks. The aim of this study was to assess the knowledge, attitude, and practice of MBBS students about Computer vision syndrome, and to identify its ocular morbidity among them.Methods: A descriptive cross-sectional survey based on the questionnaire was conducted among 1st- 4th year MBBS students of the Institute of Medicine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 0 publications
2
19
1
3
Order By: Relevance
“…The second basis was ergonomics according to Mowatt et al, 27 who conducted a study involving university students with CVS from the use of the computer and handheld devices, and determined that 75.1% of students had neck pain, and according to other authors, who concluded the same regarding both headache and neck pain from the use of the computer, mobile phone, and laptops. 26,28,29 These results were consistent with the results of our study in which subjects in the severe CVS group reported greater severity of these symptoms. The third basis was visual symptomatology according to Antona et al, 30 who conducted a study involving 54 subjects using smartphone with visual difficul-ties and determined that all scores were more unfavorable in subjects who used digital devices, and according to other authors, who conducted studies on high school students using mobile phones and laptops and determined that the percentages of these symptoms increased as the hours of digital device use increased.…”
Section: Discussionsupporting
confidence: 91%
“…The second basis was ergonomics according to Mowatt et al, 27 who conducted a study involving university students with CVS from the use of the computer and handheld devices, and determined that 75.1% of students had neck pain, and according to other authors, who concluded the same regarding both headache and neck pain from the use of the computer, mobile phone, and laptops. 26,28,29 These results were consistent with the results of our study in which subjects in the severe CVS group reported greater severity of these symptoms. The third basis was visual symptomatology according to Antona et al, 30 who conducted a study involving 54 subjects using smartphone with visual difficul-ties and determined that all scores were more unfavorable in subjects who used digital devices, and according to other authors, who conducted studies on high school students using mobile phones and laptops and determined that the percentages of these symptoms increased as the hours of digital device use increased.…”
Section: Discussionsupporting
confidence: 91%
“…Reports on university students from other parts of the world show a generally high prevalence, despite being lower than most of the studies available from the Middle East. A prevalence rate of 71.6% was reported among medical students in Nepal [ 14 ], while 80.3% of students in India majoring in medicine and engineering suffer from CVS [ 3 ]. The prevalence of CVS in the current sample could be one of the highest recorded among this age group.…”
Section: Discussionmentioning
confidence: 99%
“…The score of the digital eye strain was also found to be the highest among those who had a longer screen time, shorter screen distance and took infrequent breaks ( 4 ). In fact, university students have been documented to develop computer vision syndrome potentially due to the study burden and heavy use of digital devices, with a reported high prevalence of 71.6-94.5% ( 5 , 6 ). To our best knowledge, our study is the first to provide data regarding the impact of online learning during the SARS-CoV-2 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lockdown policy of COVID-19, foreign students took all lectures online while Chinese students have returned to the university and took lectures in classrooms. Assuming an 80% predictive prevalence ( 5 , 6 ), a 95% confidence, a 10% margin of error and a 75% response rate, we calculated the sampling size of 82 to be representative of the total population.…”
Section: Methodsmentioning
confidence: 99%